Preparation Of Poly(Lactic Acid) (Pla) Microspheres For Drug Delivery System - Tham , Cho Yin (2015)
Poly(lactic acid) (PLA) microspheres were fabricated through emulsion and solvent evaporation (ESE) technique. The particle size distributions (PSD) of microspheres obtained were in the range of 1- 250 μm, as within the range of acceptable size in parenteral injection. A shake flask method was demonstrated as an alternative technique to determine the encapsulation feasibility of an ESE system. Herein, dichloromethane-water solvent pair was used in shake flask system in order to simulate ESE system, and Rhodamine B was utilized as model drug throughout the project. In the fabrication of microspheres, the studies parameters were included PLA concentration, PVA concentration and dispersed phase volume ratio (DP). The effect of parameters on PSD range, surface morphology and encapsulation efficiency were evaluated. The optimum formulation was at 25 % DP, 15 % PLA and 1 % PVA, wherein the highest output of microspheres obtained at lowest PVA consumption in the system and narrow PSD obtained in range 1- 50 μm. In this formulation, extensive foaming of emulsion was observed during the emulsification process. It was suggested that the dispersed droplets tends to stay within the foam structure which further provide extra stabilization between droplets or partial solidified particles. The surfaces of microspheres were modified through catalytic induced hydrolysis technique. The surface and bulk properties of treated microspheres were investigated to verify the effectiveness of hydrolysis technique. Results demonstrated that the factors included timescale, type of catalyst and concentration should be manipulated in order to obtain the desired surface properties (e.g. hydrophilicity, surface charges and surface morphology) with minium deformation in microspheres bulk properti